Atlantic Sturgeon Status and Movement Ecology in an Extremely Small Spawning Habitat: The Nanticoke River-Marshyhope Creek, Chesapeake Bay. Issue 2 (16th March 2022) - Secor, D. H.; O'Brien, M. H. P.; Coleman, N.; Horne, A.; Park, I.; Kazyak, D. C.; Bruce, D. G.; Stence, C.
Abstract: Biotelemetry of Atlantic sturgeon Acipenser oxyrinchus oxyrinchus has exposed spawning behaviors in ever-smaller estuaries, surprising for the NW Atlantic's largest anadromous species. Small estuary — the Nanticoke River and Marshyhope Creek (Chesapeake Bay) — spawning-run adults and their habitat affinities are described based upon direct sampling and biotelemetry for the period 2014–2018. High rates of recapture over this period indicate a very small adult population size. Genetics revealed a very small effective population size ( N e = 12.2, 95% CI = 6.7–21.9). Most returns occurred during September at 20–27 °C. All fish departed as fall temperatures declined below 20 °C. Multi-beam sonar identified small-dispersed areas of sand-cobble and cobble, which could support adhesive embryo attachment. Movements of adults were higher during nighttime than daytime, with habitat preference for hard bottom habitats. Genetic evidence indicates that the sudden discovery of this population was unrelated to a hatchery release of several thousand juvenile sturgeon (Hudson River progeny) in 1997. The newly discovered population in the Nanticoke River exhibits a degree of resilience including multiple spawning regions and suitable spawning habitat. Still, critical vulnerabilities persist including curtailed habitat, continued agricultural and maritime development, invasive blue catfish, and a very small apparent population size. Supplemental data for this article is available online at https://doi.org/10.1080/23308249.2021.1924617